2018
DOI: 10.1016/j.ebiom.2018.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule associated protein 4 phosphorylation leads to pathological cardiac remodeling in mice

Abstract: BackgroundCardiac remodeling is a pathophysiological process that involves various changes in heart, including cardiac hypertrophy and fibrosis. Cardiac remodeling following pathological stimuli is common trigger leading to cardiac maladaptation and onset of heart failure, and their pathogenesis remains unclear.MethodsHeart specimens of tetralogy of Fallot (TOF) patients, myocardial infarction (MI) and transverse aortic constriction (TAC) mouse models were collected to determine changes of microtubule associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(67 citation statements)
references
References 38 publications
4
57
0
Order By: Relevance
“…Other groups have found that MAP4 itself becomes de-phosphorylated at serines 924 and 1056 during cardiac pathological hypertrophy, contributing to the densification of the microtubule network [124]. Contrastingly, another study reported increased phosphorylation of serines 737 and 760 during pressure overload surgery in mice [125]. Clearly the phosphorylation of MAP4 is a complicated picture, and more studies are needed to understand the relative contributions of these phosphorylation sites to MAP4 and microtubule biology.…”
Section: Microtubule Dysfunction In Cardiovascular Diseasementioning
confidence: 97%
“…Other groups have found that MAP4 itself becomes de-phosphorylated at serines 924 and 1056 during cardiac pathological hypertrophy, contributing to the densification of the microtubule network [124]. Contrastingly, another study reported increased phosphorylation of serines 737 and 760 during pressure overload surgery in mice [125]. Clearly the phosphorylation of MAP4 is a complicated picture, and more studies are needed to understand the relative contributions of these phosphorylation sites to MAP4 and microtubule biology.…”
Section: Microtubule Dysfunction In Cardiovascular Diseasementioning
confidence: 97%
“…Briefly, mice exhibiting MAP4 phosphorylation exerted age-dependent effects such as pathological cardiac remodeling, cardiomyocyte mitochondrial apoptosis and disruption, and systolic and diastolic dysfunction. As such, MT disassembly, translocation of phosphorylated MAP4, and cardiomyocyte apoptosis are deemed important factors in initiating cardiac remodeling, with the activation of p38/MAPK being suggested as the crucial upstream kinase involved in the MAP4 phosphorylation (Li et al, 2018) FIGURE 1 | Schematic illustrating the role of MAP4 in CVD. Inflammation, hypoxia, ischemia, etc., stimulate the activation of the MKK6/p38 MAPK pathway.…”
Section: Trends In Map4-mediated Cvdmentioning
confidence: 99%
“…The KI mice were constructed and identified by the Shanghai Biomodel Organism Science & Technology Development Co., Ltd. Cas9 mRNA, guide RNAs and the donor vector were microinjected into fertilized eggs (C57BL/6J) before the eggs were implanted into surrogate C57BL/6J females as described in our previous study [19].…”
Section: Generation Of the Map4 (S667a S737e And S760e) Knockin (Ki)mentioning
confidence: 99%
“…(1:1000, Bethyl, USA), p-MAP4(S768) (Biolegend, 1:1000), p-MAP4(S696) (1:1000, GL Biochem), p-MAP4(S787) (1:1000, GL Biochem), p-MAP4(S737) (1:1000, GL Biochem), β-Actin (1:1000, Cell Signaling Technology), PCNA (1:1000, Abcam), and Ki67 (1:1000, Abcam). The rabbit polyclonal antibodies against p-MAP4(S696), p-MAP4(S787) and p-MAP4(S737) were developed in house as described and validated in our previous report [19]. Here, we validated the in-house rabbit polyclonal antibody against p-MAP4 using the amino acids QAKVG(pS)LDNVGHLPAGc and the respective nonphosphorylated peptides conjugated to bovine serum albumin (BSA) ( Supplementary Fig.…”
Section: Western Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation